MICROSCOPIC OPTICAL POTENTIALS WITHIN WEAK DENSITY DEPENDENT NUCLEON-NUCLEON EFFECTIVE INTERACTIONS - Le, N. Như; Hao, T. V. Nhan (Hue University Journal of Science: Natural Science, 2017)
The microscopic optical potentials have been investigated in the framework of the nuclear structure approach based on the energy-density functional approaches. The effective phenomenological nucleon-nucleon interaction SLy5 is consistently used to obtain the Hartree-Fock single-particle states, the collective motion at small amplitudes of the target, and the coupling between the particle and phonons. The role of the weak density-dependent interaction is shown.